An Assessment of Physical Education Teacher Candidates’ Dispositions - Sofo, Seidu; Ramos, Adolfo; Thompson, Emmanuel; Pujol, Thomas J. (International Journal of Educational Technology and Learning, 2020)
The study assessed physical education teacher candidates’ (TCs) dispositions toward teaching. Participants included 72 physical education TCs (80.56% males and 19.44% females). TCs completed the Missouri Educator Profile (MEP) once, as part of the requirements for admission to the teacher education program at their institution. The MEP is a 10-point Likert scale with six subscales: Achievement (AT), Social Influence (SI), Interpersonal Effectiveness (IP), Self-Adjustment (SA), Conscientiousness (CN), and Practical Intelligence (PI). The predictor variables were TCs’ sex, PE major status, cumulative GPA (GPA), number of hours attempted (HRA), number of hours passed (HRP) at the time of taking the MEP, transfer student status (TSS), and first semester of enrollment (FSE). Descriptive data indicated that the SA subscale (45.83%) had the highest percentage of TCs with high scores, followed by SI (33.33%). Conversely, the lowest percentage of TCs with high scores was in PI (5.56%). Nonparametric rank-based regression analyses showed that sex and PE major status were significant predictors of SI, IP, and PI. Female TCs had lower scores than their male counterparts on these subscales. TCs who maintained their status as PE majors after taking the MEP had lower scores than those who changed majors. Furthermore, HRA and HRP significantly predicted the IP and PI subscales. TCs with higher number of hours attempted had higher scores on the IP and PI subscales. Conversely, the higher the number of hours passed, the lower the score on the IP and PI subscales. All the predictor variables were not significant for subscales AT, SA, and CN. Finally, transfer student status was not a significant predictor of any of the dispositions. Physical Education Teacher Education programs need to teach and assess TCs’ dispositions on a regular basis. Dispositional assessment data could serve as valuable source of feedback for teacher education program improvement.